Avaliação de dois clones de Escherichia coli recombinante quanto ao crescimento e expressão de antígenos de Leishmania chagasi (kmp11 e P36) - Chaves, Roberta Viana Araújo (2009)
Visceral leishmaniosis caused by Leishmania chagasi, also known as calazar, presented, in the period from 1990 to 2005, tax of incidence in Brazil varying between 1 and 3 cases for 100 000 inhabitants. The Northeast region that up to the year of 2000 contributed with almost 90% of the registered cases is reducing his participation in the current decade, reaching 56% in 2005. Conventional leishmaniasis treatment is costly and it shows high toxicity, demanding more research for alternative treatments, with special interest in development of vaccines and diagnosis kits which include production of recombinant antigens by host cells. Escherichia coli has been the microorganism most studied and used as a host for recombinant protein production. Therefore, the aim of this work was to study the influence of induction on cellular growth and to verify the type of Leishmania chagasi antigens expression (intra or extracellular) during two recombinant E. coli clones (kmp11 and P36) cultivation in rotary incubator (shaker) using three different media (2xTY, TB, FASS+EL). For that, tests were carried out using conditions established in the literature for E. coli (37°C and 200 rpm) and media supplemented with antibiotics to guarantee that only competent cells grows. First, tests were carried out without induction in order to verify the two microorganisms kinetic behavior (growth and substrate consumption) in different media. Next, the induction was carried out through the addition of IPTG (1mM as final concentration), at the first hour of cultivation. It was observed that protein expression were intracellular for all clones and media tested, however the highest level of expression was clearly observed by the electrophoresis band density (intensity) for 2xTY medium and kmp11 protein. Although it contains the lowest substrate concentration, consequently, a reduced cellular concentration when compared to other media, it appeared that this medium and clone combination is the most indicated for recombinant protein production. Therefore, the objective of this work was achieved, since the interested proteins were produced. Consequently, this result motivates new studies for production optimization using different cultivation strategies